QUALITY MANAGEMENT IN THE IMPROVEMENT OF PUBLIC HEALTH IN BASIC HEALTH UNITS - Bezerra, Tamires Almeida; Morais, Ângela Zenúbia Pereira de Araújo; Simão, Robson Albano; da Silva, Mara de Jesus Costa; Leite, Juliana Maria de Oliveira; Nascimento, Ageu Quintanilha Viana; de Sousa Júnior, José Soares; Baliana, Leticia de Oliveira; dos Anjos, Elziane Mota; Leite, Teresa Cristina de Oliveira; Viana, Suely Maria do Nascimento; Santiquio, Camila da Silva Nunes (Seven Editora, 2026)
Introduction: Quality Management plays a crucial role in improving public health, especially in Basic Health Units (UBS), where primary care plays a key role in health promotion and disease prevention. In view of the above, this study is justified by its academic, scientific and social relevance, based on presenting the main outcomes related to the subject in question. Through a comprehensive and critical review of the literature, the main challenges and benefits associated with the implementation of a quality management system in the UBS will be analyzed, as well as the most effective strategies to promote the continuous improvement of health services and achieve more care. humanized and efficient for the population. Objective: To address the importance of quality management in improving public health in Basic Health Units. Methodology: This is an integrative literature review research, carried out through a survey of data in the scientific bases: LILACS, PUBMED and SCIELO. Results and Discussion: Based on the literature analysis, the main outcomes for this discussion were selected. Based on this, the literature has shown that based on quality management, it is possible to establish indicators and measures that allow an objective evaluation of the results achieved, as well as identifying areas for improvement and making decisions based on specific data. Implementing quality management in healthcare services involves applying practices, processes, and policies to ensure that the organization’s services meet or exceed the care needs of patients. It is important to emphasize that the implementation of quality management is an ongoing process that requires the commitment of the entire team to achieve effective results. Conclusion: It is evident that the implementation of quality management promotes the standardization of processes, the use of best practices and the adoption of evidence-based clinical guidelines, directly impacting the effectiveness of treatments and increasing patient safety. DOI: https://doi.org/10.56238/sevened2026.001-019